Uji Daya Terima Aneka Frozen Food Berbahan Dasar Tempe sebagai Alternative PMT Balita - hesti Atasasih; Irma Susan Paramita; Fitriani Fitriani (Jurnal Kesehatan Komunitas, 2023)
Indonesia is the world's largest producer of tempeh and the largest soybean market in Asia. As much as 50% of Indonesia's soybean consumption is in the form of tempeh. The proteins found in tempeh are relatively easy to digest. Frozen food can be a solution in extending the shelf life and durability of a product and causing food to become durable and not easily decompose. The purpose of this study is to find out the receiving power of frozen food tempeh as an alternative to toddler supplements in an effort to prevent stunting. This study was an experimental study using RAL (Complete Randomized Design) with one control and 3 treatments, 30%, 50%, and 70%. Furthermore, hedonic tests are conducted on each frozen food and proximal tests on frozen foods are most preferred to find out carbohydrate levels, protein levels, fat content, water content, and ash levels. The results showed that the most preferred treatment in terms of color, aroma, taste, and texture of frozen food meatballs was with the addition of 50% tempeh (P2), while for the nugget and ball groups, the most preferred panelists were the addition of 70% tempeh (P3). Kruskall Wallis test results showed the addition of tempeh gives a noticeable influence on the level of fondness for the color, aroma, taste, and texture of tempeh meatballs, nuggets of tempeh, and tempeh balls.